Active Antibacterial Fraction from Ethanolic Extract of Johar Leaves (Cassia siamea Lam.) against Staphylococcus epidermidis and Its Bioautography - Munawaroh, Rima; Khoirunnisa, Khoirunnisa (Pharmacon: Jurnal Farmasi Indonesia, 2023)
Johar leaves (Cassia siamea Lam.) have been traditionally used to treat pruritus due to their antibacterial properties. This study aims to identify the active fraction of an ethanolic extract of Johar leaves against Staphylococcus epidermidis, as well as the active chemical class. The extraction process involved maceration with 96% ethanol. The liquid-liquid extraction method was used to separate the n-hexane, ethyl acetate, and water fractions. The resulting extract and fraction were assessed for antibacterial activity using the well diffusion method. Sample loadings of 4 mg, 2 mg and 1 mg per well were used, with DMSO as a negative control and 6 mg chloramphenicol as a positive control. The test results indicate that the ethyl acetate fraction is more effective than the extract. Specifically, the fraction produced an inhibition zone of 13.5 ± 0.5 mm at a loading of 4 mg/well, while the extract only produced an inhibition zone of 9.3 ± 1.2 mm at the same loading. Additionally, there was a significant difference in the diameter of the inhibitory zone between treatment groups at p 0.05. The TLC results indicate that the ethyl acetate fraction of Johar leaves contains alkaloid, phenolic, flavonoid, and steroid compounds when using silica gel 60 F254 stationary phase and chloroform:ethyl acetate:ethanol (7:2:1 v/v/v) mobile phase. Bioautography results showed that the phenolic and alkaloid compounds at Rf 0.22 and phenolic compound at Rf 0.42 are responsible for the antibacterial activity against Staphylococcus epidermidis.